Comparative study of Malaysia human capital with selected ASEAN and developed countries: a fuzzy TOPSIS method - Lai, Wei Sieng; Ishak Yussof (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Comparative study on human capital performance between countries is important especially for developing countries to measure their gap with developed countries. This article uses the unconventional TOPSIS method to compare Malaysia and other selected countries in terms of human capital achievement with education being the main measure of human capital. Results indicate that Malaysia is doing great among her ASEAN peers but more need to be done in order to catch up with the developed nations.